Evaluating the Effectiveness of Public-private Partnership Projects at The Regional Level ("Journal "U". Economy. Management. Finance.", 2020)
The article is devoted to the peculiarities of evaluating the effectiveness of regional public-private partnership projects aimed at the development of infrastructure facilities in the context of socio-economic development of regions, based on the generalization of joint goals, objectives, benefits and risks, as well as a quantitative assessment of economic efficiency for both sides.
Keywords: public-private partnership; economic efficiency; PPP; regional development; private investment